MICROWAVE DRYING OF PLANT TISSUE FOR NUTRITIONAL ANALYSIS OF Corymbia citriodora (HOOK.) AND Hevea brasiliensis MUELL. ARG. - Teixeira, Matheus Pozetti [UNESP]; Silva Campos, Cid Naudi; Prado, Renato de Mello [UNESP]; Caione, Gustavo; Checchio Mingotte, Fabio Luiz [UNESP]; Agostinho, Flavia Bastos (Colegio Postgraduados, 2017)
The method used to dry plant tissue samples may modify its nutrient content, and results in incorrect diagnostic of crop nutritional status. The hypothesis was that microwave drying method does not affect the nutrient content of leaves neither the interpretation of the results, as compared to oven-drying procedure. In this study we evaluated the effect of microwave drying of eucalyptus (Corymbia Citriodora (Hook.)) and rubber trees (Hevea brasiliensis Muell. Arg.) leaves on dry matter and macronutrient content, as compared to oven drying. The study was performed in a laboratory at the Department of Soils and Fertilizers of Universidade Estadual Paulista Julio de Mesquita Filho, UNESP, JaboticabalSP- Brazil. The experiments were: one using leaf samples of eucalyptus and other using leaf samples of rubber trees. The experimental design was completely randomized and treatments were drying in conventional oven and in microwave oven, with 10 repetitions. Data were analyzed using ANOVA and treatments means were compared with F test and Tukey test (p <= 0.05). The dry matter and the macronutrient content of each sample were determined. There were no differences between the drying methods on leaf nutrient content, except for N content of rubber trees. Similar dry matter content was obtained for rubber trees and eucalyptus samples. Microwave drying is useful as an alternative method to dry plant tissues samples aiming to its chemical analysis.
Keywords: chemical analysis; dry matter; nutritional status; plant material; plant nutrition